Peran Pembangunan Ekonomi dalam Membentuk Sumber Daya Manusia yang Unggul di Indonesia - Aini Zaqiyah; Ahmad Gianto; Nurus Sobakh (Indonesia Economic Journal, 2026)
Economic development plays a crucial role in improving the quality of human resources (HR) in Indonesia. Sustainable economic growth enables increased access to education, healthcare, and decent employment, thus improving skills, productivity, and public welfare. Furthermore, economic development encourages innovation and technological mastery to face global competition. However, various challenges remain, such as development inequality, low education quality in some regions, and limited access to economic opportunities. Therefore, synergy between the government, the private sector, and the community is needed to create inclusive and sustainable policies. Thus, economic development is oriented not only toward growth but also toward improving the quality of human resources, the nation's primary asset.